Optimization of headspace for GC‐MS analysis of fragrance allergens in wooden children's products using response surface methodology. Issue 1 (25th January 2019) - Li, Meiping; Li, Rong; Wang, Zhijuan; Zhang, Qing; Bai, Hua; Lv, Qing
Abstract: Residual chemicals in wooden children's products may threaten children's health, but few studies have paid attention to it so far. In this study, a simple and green method was developed for the determination of volatile chemicals, especially the 48 fragrance allergens in wooden children's products using static headspace coupled with gas chromatography and mass spectrometry. Minimal amounts of sample (20 mg) and acetone solvent (40 μL) were used, and no additional sample pretreatment was performed except for freezing and grinding. Three factors (incubating temperature, equilibration time, pressing pressure) affecting headspace extraction were optimized by response surface methodology to obtain scientific results considering of the interactions among variables. Under the optimum detection conditions, this method was successfully validated for the analysis of fragrances. The proposed method showed limits of quantification within the range of 0.2–20 mg/kg. Recoveries ranged from 79.8 to 115.2%, and the relative standard deviation (n = 5) varied from 0.6 to 9.9%. Moreover, interferences caused by different sample matrices were investigated. The method was further applied to the analysis of 30 commercial wooden samples. Results demonstrated the existence of fragrances in wooden children's products. Benzyl alcohol, trans ‐2‐heptenal, eugenol, and isoeugenol were the compounds with high detection rate.